Pengaruh Tingkat Pendidikan, Pemahaman Teknologi Informasi, Persepsi Pelaku UMKM, Motivasi, dan Sosialisasi Terhadap Implementasi SAK EMKM dalam Laporan Keuangan UMKM - Leatemia, Senda Yunita; Gainau, Paskanova Christi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
SAK EMKM, which is an abbreviation for Financial Accounting Standards for Micro, Small and Medium Enterprises, functions as a collection of standards designed to be a reference for financial accounting practices among MSMEs. However, many business actors still have limited knowledge and understanding in managing MSME finances. This research aims to examine the influence of education level, understanding of information technology, perceptions of MSME actors, motivation, and socialization of SAK EMKM on the implementation of SAK EMKM. This research was conducted in order to answer problems related to the implementation of SAK EMKM in the financial management of MSMEs. The sample for this research is MSMEs in Ambon City. This research was conducted from October to December 2024, using a purposive sampling technique and the sample size was determined using the Slovin formula, with the number of respondents being 100 MSME actors. The data collection technique uses survey techniques through distributing questionnaires, while the data analysis technique in this research is multiple linear regression analysis using SPSS support. The findings of this research indicate that the level of education, understanding of information technology, perceptions of MSME actors, motivation, and socialization of SAK EMKM can partially influence the implementation of SAK EMKM. Based on the results of the study, the level of education of MSME actors plays the most important role in implementing MSME SAK in managing their business finances.